Using MySQL for learning management system - Saudi, Azali; Tanalol, Siti Hasnah; Tahir, Asni (2004)
The Internet provides a new way of getting access to knowledge resources and materials.The Internet platform is proven provides an efficient way of communication among instructors, students and management using computers via network. However, an integrated learning management system (LMS) is required in order to have an efficient and effective communication, and to fully utilize the facilities provided by the Internet.There are already several implementations of such system, which are developed for commercial purpose, specifically for an organization or even provided in the public domain.This paper describes our work in utilizing open source tools particularly MySQL database, to develop web-based learning management system. The main focus is to evaluate the performance of MySQL, ease of usage, and platform dependency in a medium scale project.